Sleep disturbances and female gender predict a poor quality of life in Iraqi contact dermatitis patients: A cross-sectional study - Ahmed Al-Imam; Mohammed H Al-Baghdadi; Sama T Abdullah; Sama H Al-Jawhar; Michal Michalak (Wolters Kluwer Medknow Publications, 2023)
Background: Contact dermatitis is a form of eczema triggered by an allergen or an irritant substance. Its impact on the quality of life (QoL) is unknown among Iraqi patients. Purpose: We aim to survey the QoL among Iraqi contact dermatitis patients and infer the risk factors influencing it. Methods: The current study is cross-sectional among patients admitted to Baghdad Medical City. We used the dermatology life quality index to assess the QoL and collected parameters related to socio-demographics and other eczema-related factors. Results: A hundred patients (males = 43%; females = 57%) were in the third decade of life (total = 34 ± 0.97; males = 33 ± 1.5; females = 34 ± 1.3). The multivariable logistic regression had good statistical accuracy and satisfied the Hosmer-Lemeshow goodness-of-fit test (Nagelkerke's R2 = 0.13, statistical accuracy = 67%, P = 0.47). Three factors associated with an impaired QoL, including sleep disturbances (odds ratio [OR] =4.8, 95% confidence interval [CI] [1.3, 18], P = 0.021), female gender (OR = 2.6, 95% CI [1.1, 6.4], P = 0.036), and family size (≤4 members) (OR = 3.2, 95% CI [0.99, 10], P = 0.053). Females with contact dermatitis who experience sleep disturbances and live in small households are more likely to suffer from severely impaired QoL. Conclusion: The QoL among Iraqi contact dermatitis patients is influenced by sleep disturbances, female gender, and family size.